The Disability Advocacy of the National Council of Churches - Herzog, Albert A. (Journal of religion, disability & health, 2006)
Since 1950, the National Council of Churches has worked ecumenically to foster numerous ministries among people with disabilities, both nationally and among its member communions. Its original emphasis was focused on the Christian education of children and adults with physical and developmental disabilities. Gradually, through exposure to other issues faced by persons with disabilities, and through involvement with secular and religious agencies, the Council's work expanded to include a wide variety of disability-related issues, including the International Year of Disabled Persons. Today, the Council's work involves denominational representatives beyond its member communions and has become increasingly integrated into the full agenda of the National Council of Churches.